Trend to efficacy and safety using antithrombin concentrate in prevention of thrombosis in children receiving l-asparaginase for acute lymphoblastic leukemia - Mitchell, Lesley; Andrew, Maureen; Hanna, Kim; Abshire, Thomas; Halton, Jacqueline; Wu, John; Anderson, Ron; Cherrick, Irene; Desai, Sunil; Mahoney, Donald; McCusker, Patricia; Chait, Peter; Abdolell, Mohamed; Veber, Gabrielle de; Mikulis, David (Thrombosis and Haemostasis, 2003)
An association has been reported between thrombotic events and the use of L-asparaginase (ASP) in children with acute lymphoblastic leukaemia (ALL). The mechanism for thrombosis is likely related to an acquired antithrombin deficiency. Since a primary prophylaxis using antithrombin concentrates may prevent thrombosis, the PARKAA (Prophylactic Antithrombin replacement in kids with ALL treated with L-asparaginase) study was performed. The objectives of PARKAA were to determine if there was a trend to efficacy and safety of antithrombin treatment as assessed by 1) incidence of thrombosis 2) incidence of bleeding and 3) plasma markers of endogenous thrombin generation as surrogate outcomes for thrombosis. The study was not powered to answer the question of efficacy and safety, but rather to detect a trend. PARKAA was an open, randomised, controlled study in children with ALL being treated with ASP.Children were randomised to receive antithrombin infusions or no antithrombin treatment. All thrombotic events were confirmed using bilateral venography, ultrasound, echocardiography and MRI. The incidence of thrombosis in patients treated with antithrombin was 28% (95% CI 10-46%), compared to 37% (95% CI 24-49%) in the non treated arm. Two minor bleeds occurred in patients in the treated arm, but were not considered to be related to antithrombin. No significant differences were seen in plasma markers by the treatment group. In conclusion, treatment with antithrombin concentrate shows a trend to efficacy and safety. In contrast, there was no difference in surrogate markers for thrombosis. Carefully designed clinical trials are needed to test the efficacy and safety of antithrombin in this population.
Keywords: Thrombosis; paediatric; acute lymphoblastic leukemia; L-asparaginase; antithrombin concentrate